Effects of therapeutic ultrasound for knee osteoarthritis: a systematic review and meta-analysis. (December 2019) - Wu, Yu; Zhu, Shibo; Lv, Zenghui; Kan, Shunli; Wu, Qiuli; Song, Wenye; Ning, Guangzhi; Feng, Shiqing
Objective: To assess the effectiveness and safety of therapeutic ultrasound with sham ultrasound on pain relief and functional improvement in knee osteoarthritis patients. As phonophoresis is a unique therapeutic ultrasound, we also compared the effects of phonophoresis with conventional non-drug ultrasound. Data sources: PubMed, EMBASE, and the Cochrane Library were systematically searched for randomized controlled trials from inception up to June 2019. Review methods: Randomized controlled trials comparing therapeutic ultrasound with sham ultrasound in knee osteoarthritis patients were included. Phonophoresis in the experimental and control groups were compared through conventional ultrasound, and corresponding trials were also included. Two reviewers independently identified eligible studies and extracted data. Risk of bias assessments and therapeutic ultrasound safety assessments were also performed. Results: Fifteen studies including three phonophoresis-related studies with 1074 patients were included. Meta-analyses demonstrated that therapeutic ultrasound significantly relieved pain ( P < 0.00001) and reduced the Western Ontario and McMaster Universities (WOMAC) physical function score ( P = 0.03). In addition, therapeutic ultrasound increased the active range of motion ( P < 0.00001) and reduced the Lequesne index ( P < 0.00001). Subgroup analysis of phonophoresis ultrasound illustrated significant differences on the visual analogue scale ( P = 0.009), but no significant differences on WOMAC pain subscales ( P = 0.10), and total WOMAC scores were observed ( P = 0.30). There was no evidence to suggest that ultrasound was unsafe treatment. Conclusions: Therapeutic ultrasound is a safe treatment to relieve pain and improve physical function in patients with knee osteoarthritis. However, phonophoresis does not produce additional benefits to functional improvement, but may relieve pain compared to conventional non-drug ultrasound.